Análisis del uso de inhibidores para mitigar la corrosión interna en tuberías de aguas de formación petrolera (2020)
The deterioration of steel pipes to coal due to internal corrosion is one of the main problems in ensuring the integrity and the useful life of the oil field installations, thus generating an economic impact, affecting the costs of remedial maintenance of the infrastructure. For this reason, an analysis of different inhibitors used in the industry is carried out to reduce and control the corrosion caused by the composition of the formation water present in the production wells. The bibliographic diagnosis of the main corrosion mechanisms, which originate from the presence of fouling compounds, sulfates, ions and dissolved gases, was carried out for its elaboration. Implementing a comparison of inhibitors under the prioritization matrix, which identifies influential parameters for the choice of inhibitory compound, includes efficiency, costs, concentration, pH of the corrosive medium, solubility, toxicity, determining the inhibitor BIFP (Imidazole compound) with the best weighted score of 4.74 according to the criteria evaluated from documented experimental research. Finally, an estimate of costs was made with the implementation of the BIFP inhibitor taking into account labor, costs for purchasing equipment, maintenance, product, transportation and other criteria.